Medición del nivel de satisfacción de los clientes de la cooperativa de ahorro y crédito “Focash Ltda. de la ciudad de ShushufindiMedición del nivel de satisfacción de los clientes de la cooperativa de ahorro y crédito “Focash Ltda. de la ciudad de Shushufindi. - Jiménez Quintanilla, Gilma Yolanda (2017)
The general objective of the present investigation is to measure the level of satisfaction of the customers of the Cooperative of Savings and Credit "FOCASH" Ltda., Of the city of Shushufindi, the same one that allows to determine the current state of the cooperative "FOCASH LTDA . "That serves as a guide for the application of a model measuring the level of satisfaction of the clients and leads to obtain the silver targets A current analysis of the company was made, which allowed to know the influence of customer satisfaction on the development of the cooperative, to then develop the SWOT analysis, competitiveness index and finally make a satisfaction proposal for the Savings Cooperative and Credit "FOCASH" LTDA. For the exposed methods and techniques were applied, within the first used the scientific method, the inductive methods, the deductive method, the historical methods, the synthetic method and the statistical method; and, as for the techniques, the bibliographic research, the interview made to the Manager and the survey made to the clients of the Cooperative were applied. Among the main results obtained in the project under study, it can be mentioned that the credit union "FOCASH" LTDA, is an entity that has good influence in the environment where it is developed. However, it faces difficulties such as low capital investment, there is no adequate knowledge of the market in which it operates, customer loyalty. In the same way, it was determined that the credit union "FOCASH" LTDA, does not have a process management system, that the provision of its services must improve, that there is a percentage of 66.67% of dissatisfaction, Regarding the costs it charges for its services, 59.90% do not agree with it. Finally, solution strategies were proposed that would improve the satisfaction of the members of the Cooperative; therefore, to carry out these strategies, the directors of the credit union "FOCASH" LTDA, should invest in increasing the portfolio of products and services, design a process management system, train staff and acquire ATMs to expedite customer service.